Volume 8: 28th Conference on Mechanical Vibration and Noise 2016
DOI: 10.1115/detc2016-59467
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting From Torsional Vibrations Using a Nonlinear Oscillator

Abstract: Harvesting ambient energy in a variety of systems and applications is a relatively recent trend, often referred to as Energy Harvesting. This can be typically achieved by harvesting energy (that would otherwise get wasted) through a physical process aiming to convert energy amounts to useful electrical energy. The harvested energy can be thermal, solar, wind, wave or kinetic energy, with the last class mainly referring to harvesting energy from vibrating components or structures. More often these oscillations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Magnetic levitation was used, as in Mann and Sims, 21 to achieve a duffing-type nonlinear system. Alevras et al 22 found that variation in stiffness, in combination with asymmetric forcing, leads the concept described in Gunn et al 20 to multiple resonance zones, comprising mono-stable and bi-stable dynamics. In another work, Alevras et al 23 investigated the nonlinear dynamics of the Mathieu oscillator, also considering cubic stiffness for broadband energy harvesting.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Magnetic levitation was used, as in Mann and Sims, 21 to achieve a duffing-type nonlinear system. Alevras et al 22 found that variation in stiffness, in combination with asymmetric forcing, leads the concept described in Gunn et al 20 to multiple resonance zones, comprising mono-stable and bi-stable dynamics. In another work, Alevras et al 23 investigated the nonlinear dynamics of the Mathieu oscillator, also considering cubic stiffness for broadband energy harvesting.…”
Section: Introductionmentioning
confidence: 93%
“…Masuda et al 19 have developed a control system that tracks the higher energy stable branch of a duffing mechanical oscillator, thus improving the power output of the harvester over a wide frequency range. Gunn et al 20 presented an electromagnetic energy harvester concept for a rotating propulsion system shaft. Magnetic levitation was used, as in Mann and Sims, 21 to achieve a duffing-type nonlinear system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, a number of studies have addressed this problem, proposing the intentional use of nonlinearities in the system stiffness. [5][6][7] Nonlinear oscillators are wellknown in the hysteretic response, which enables multiple stable solutions to co-exist over a wide range of frequencies. The physical properties of nonlinear dynamical systems such as bi-stability or stochastic resonance have also been suggested in order to improve the performance of vibration energy harvesters.…”
mentioning
confidence: 99%